2013
DOI: 10.2147/ndt.s42426
|View full text |Cite
|
Sign up to set email alerts
|

Effects of primary caregiver participation in vestibular rehabilitation for unilateral neglect patients with right hemispheric stroke: a randomized controlled trial

Abstract: IntroductionThe current study aims to investigate the effects of primary caregiver participation in vestibular rehabilitation (VR) on improving the measures of neglect, activities of daily living (ADL), balance, and falls of unilateral neglect (UN) patients.MethodsThis study is a single-blind randomized controlled trial. Both experimental (n = 24) and control groups (n = 24) received conventional rehabilitation. The experimental group undertook VR for a month. During the first and second weeks, a registered nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 36 publications
1
27
0
12
Order By: Relevance
“…The Cawthorne-Cooksey exercises (Cooksey, 1946) were used by Dai and colleagues (2013) to vestibular rehabilitation of stroke patients with hemineglect. These exercises encompass several steps: (a) to move the head up and down and to both sides with eyes open; (b) same as previous with eyes shut; (c) same as previous while looking at a moving target.…”
Section: Resultsmentioning
confidence: 99%
“…The Cawthorne-Cooksey exercises (Cooksey, 1946) were used by Dai and colleagues (2013) to vestibular rehabilitation of stroke patients with hemineglect. These exercises encompass several steps: (a) to move the head up and down and to both sides with eyes open; (b) same as previous with eyes shut; (c) same as previous while looking at a moving target.…”
Section: Resultsmentioning
confidence: 99%
“…There was a statistically significant difference between the groups ( p < 0.05). Dai et al [ 22 ] reported that the mean balancing exercise score had increased from 12.88 points to 19.29 points with virtual rehabilitation and trunk stability-based upper limb training, showing a significant difference. Wee et al [ 10 ] reported that when the upper limb reaches an object within its length, the shoulders and elbows stretch, and the center of gravity of the arm deviates from the center of gravity of the body.…”
Section: Discussionmentioning
confidence: 99%
“…A similar small study with some different methodology, interventions and primary outcome demonstrated that individuals with neglect after right hemispheric stroke, through participation in VR, improved regarding the degree of neglect, ADL and balance [36]. However, both the VR and control groups in that study improved in balance but there were no statistically significant differences in improvement between the groups and they did not use data on self-rated health.…”
Section: Discussionmentioning
confidence: 93%